Positioning UK research and technology organizations as outward‐facing technology‐bases. (28th December 2015) - Readman, Jeff; Bessant, John; Neely, Andy; Twigg, David
Abstract : UK research and technology organizations (RTOs) compete globally by offering engineering, technology and innovation services. Although associated historically with specific industries, UK RTOs have expanded into nontraditional markets and sectors. This article profiles 15 UK RTOs and we suggest that UK RTOs have unique technology and innovation capabilities, which cut across industrial boundaries.